FEATURES OF THE ABDUCTION MECHANISM WORK BEFORE AND AFTER TOTAL HIP JOINT ARTHROPLASTY - Tyazhelov, O.A.; Karpinska, O.D.; Goncharova, L.D.; Klymovytskyi, F.V. (World of Medicine and Biology, 2020)
Increased tone of the flexors and adductor muscles of the hip in combination with a decrease in elasticity and contractile function of abductors and protractors of the hip due to contracture of the hip joint leads to imbalance in the muscles of the pelvic girdle, which negatively affects the positional adaptation of endoprosthesis components during the surgery and complicates the postoperative period in patients. The treatment results analysis of 114 patients with diseases of the hip joint showed that in most patients the manifestations of pelvic girdle muscle deficiency after hip arthroplasty decreased, but did not disappear for a long time. The study of vertical posture in patients with normal and reduced size of the total femoral offset after hip arthroplasty showed that the reduction of the abductor shoulder leads to a significant change in the main indices of the stabilogram, namely to increased energy expenditure to maintain vertical posture, therefore energy depletion occurs faster. It is clinically manifested by symptoms of pelvic girdle muscle insufficiency - lameness, positive symptom of Trendelenburg, Duchenne, the need to use additional support, etc.